Auditory Brainstem Evoked Response Patterns in the Neonatal Intensive Care Unit - Mohammed, Somia Tawfik; El-Farrash, Rania Ali; Taha, Hesham Mohammed; Moustafa, Omaima Ahmed (American Journal of Perinatology, 2020)
Objective Delayed maturation of auditory brainstem pathway in neonates admitted to the neonatal intensive care unit (NICU) may lead to misdiagnosis of children with normal peripheral hearing and inappropriate use of amplification devices. The aim of this study is to determine the pattern of auditory brain stem response in neonates admitted to the NICU for proper hearing assessment in this high-risk population.Study Design This prospective study was conducted on 1,469 infants who were admitted to the NICU, of which 1,423 had one or more risk factors for permanent congenital hearing loss and were screened with automated auditory brain stem response (AABR). A total of 60 infants were referred for diagnostic ABR analysis after failure on AABR screening. The control group comprised 60 well-baby nursery neonates with no risk factors for PCHL.Results Mean values of absolute latencies of waves III and V; interpeak latencies I–III, III–V, and I–V; amplitude of waves I, and V; and I/V amplitude ratio at 90 dBnHL measured for the right and left ears at 1 and 3 months of age show significant difference in NICU neonates compared with controls (p < 0.05). All the diagnostic ABR measurements significantly improved at the age of 3 months (p < 0.001) except wave I absolute latency of both groups (p > 0.05). Significant correlations were found between ABR readings at the age of 1 and 3 months and the gestational age of the NICU neonates (p < 0.05).Conclusion Diagnostic ABR findings in NICU neonates suggested delayed maturation of the auditory brainstem pathway with a great impact of gestational age on this maturation. Auditory maturational changes were observed at 3 months of age of patient and control groups.
Keywords: hearing assessment; auditory brainstem response; permanent congenital hearing loss; auditory maturational changes; brain function